Interpreting Indonesian Domestic and Foreign Policies: New Prospects for Democratization in the 1990s? - Pambagyo, lman (My University, 1996)
As the world approached the end of the 1980s, human rights and democracy became major issues not only within the Third World countries, but also in international relations. lt was in this newly emerging environment that Indonesians found themselves at the centre of a prolonged debate about, on the one hand, the need to maintain strict political control to enable the country to catch up with the more developed countries and, on the other hand, the need to democratize the existing political system to accommodate increasing national and international pressures for more democratic governance. This thesis is of the opinion that, contrary to the pessimistic views held by some scholars, Indonesia will inevitably democratize in the future, although the process of democratization will proceed only gradually and cautiously, under Indonesia's own terms, and towards Indonesia's own form of democracy that blends some basic values and norms of Western democracy with indigenous values and norms. This thesis focuses on the four, most commonly discussed factors influencing democratization-socioeconomic development, international factors, the role of the elite, and political culture. However, since domestic politics does not take place in an international vacuum, and because international interference in domestic politics of the Third World countries is not always welcomed by the latter, this thesis also gives special attention to the realm of Indonesian foreign policy and relates it to the issues of democratization. A central feature of this thesis is to understand Indonesian political culture and the elites of the Suharto government. lt will be contended that, while socioeconomic and international factors make it increasingly difficult for the present government to maintain its strict political control over the population, Indonesian political culture and the persistence of elites' interests leave litfle room for revolutionary, large-scale, foreign-influenced democratization to take place.
Keywords: Political Science; Political Science